A Model Humanitarian Cleft Mission. Issue 3 (March 2015) - Fayyaz, Ghulam Qadir; Gill, Nauman Ahmad; Ishaq, Irfan; Ganatra, Muhammad Ashraf; Mahmood, Farrakh; Kashif, Muhammad; Alam, Iftikhar; Chen, Philip Kuo-Ting; Lo, Lun-Jou; Laub, Donald Rudolph
<x xml:space="preserve">Abstract</x> Background: There are many countries in the world where patients with cleft lip and palate cannot get access to specialized cleft care units. Cleft missions play an important role in providing surgical care to the areas of the world with limited resources. This article presents a model of cleft missions that can be adopted in many countries where expertise is available but resources are limited. Through proper utilization of local human resource, this type of mission can be a cost-effective and robust way of treating patients with cleft in countries with approximately 52% of the world's population. Methods: We present a case series of patients of one of our cleft missions carried out in Khairpur, Pakistan, in March 2014 over a period of 7 days. Specific details concerning the organization of mission, gathering of patients, preparation for surgery, and carrying out surgical procedures in a safe and swift manner are presented. Results: A total of 312 patients were operated on in 7 days. There were 145 patients with cleft lip and 167 patients with cleft palate. There were 187 male and 125 female patients with mean age of 7 years. Contemporary operative techniques were utilized to repair different types of cleft lip and palate. Of 167 patients, only 16 developed fistula. Conclusion: A locoregional cleft team can be more effective to care for the patients with cleft in countries where surgical and other expertise can be utilized by proper organization of cleft missions on a national level.